The impact of robot-assisted treadmill therapy on urinary incontinence rates in a child with lower limb paresis – a single case study - Jung, Michael W.; Schön, Verena (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Bladder incontinence is a daily challenge for spinal cord injury patients. An initial single case study showed the positive eﬀects of robot-assisted gait training in an adult with this issue. The current study aimed to evaluate possible correlations between Lokomat®Pro treatment and incontinence in a seven-year-old boy with incomplete paraplegia at T10 caused by menin-goencephalitis.Methods. The study used an A-B-A-B-A-E design and observed the patient over a 17-week period. The intervention involved two 4-week blocks with the Lokomat®Pro interspersed by a wash-out phase of 3 weeks, with a ﬁnal 5-week wash-out phase. Follow-up analysis included the Janda muscle function test, the 10-meter walk test (in crawling), surface sensitivity assessment, and the Patient Speciﬁc Functional Scale (PSFS) combined with the Canadian Occupational Performance Measure (COPMa-kids) at each measurement time point. The patient also received 60 min of standardised gait training daily.Results. The results show a positive relationship between therapy and muscle function, with an impressive increase in bladder maximum ﬁlling volume. Furthermore, nocturnal diaper wetting disappeared under therapy, with the patient able to sleep through the night without the need for a diaper change. In addition, stool consistency returned to normal during treatment.Conclusions. The therapy proved an eﬀective treatment by reducing incontinence and positively inﬂuencing muscles. Subse-quent studies, with more cases, should aim to conﬁrm these eﬀects.
Keywords: bladder control; children; incontinence; Lokomat®Pro; spinal cord injury; treadmill therapy